Тренінг у формуванні комунікативної культури майбутніх фахівців інженерних спеціальностей - Галацин, Катерина; Фещук, Алла; Halatsyn, Kateryna; Feshchuk, Alla (Східноєвропейський національний університет імені Лесі Українки, 2017)
Комунікативна культура особистості майбутнього фахівця є однією із важливих складових професійної культури особистості, а відтак проблема формування комунікативної культури майбутніх інженерів є актуальною. Метою статті є розкриття ролі тренінгів у формуванні комунікативної культури майбутніх фахівців інженерних спеціальностей. У статті розкривається сутність тренінгу як одного із інтерактивних методів, подається його структура, аналізується специфіка застосування у навчально-виховному середовищі ВТНЗ з метою формування комунікативної культури студентів; окреслюються основні вимоги щодо проведення тренінгу. У висновках визначені основні напрями ефективного застосування тренінгів у формуванні комунікативної культури майбутніх інженерів. The communicative culture of the identity of the future specialist is one of important components of the professional culture of the personality and consequently, the problem of formation the communicative culture of the future engineer is urgent. The purpose of the article is disclosure a role of trainings in formation of the communicative culture of the future specialists in engineering. In article the essence of a training as one of interactive methods reveals, its structure is represented, specifics of the applications for the educational environment in higher technical educational institutions with the purpose of formation the communicative culture of students are analyzed; the main requirements concerning holding the training are determined. In conclusions the main ways for the effective application of training in the formation of communicative culture of future engineers are determined.
Training in formation the communicative culture of future specialists in engineering
Keywords: комунікативна культура; формування комунікативної культура; вищий технічний навчальний заклад; інтерактивні методи; тренінг; communicative culture; formation of the communicative culture; higher technical educational institution; interactive methods; training